Contested spaces of nobility in early modern Europe - Romaniello, Matthew P.; Lipp, Charles T. (Ashgate, 2011)
The spaces of nobility / Matthew P. Romaniello and Charles Lipp -- The early modern European nobility and its contested historiographies, c. 1950-1980 / Hamish Scott -- Negotiating for Agnes' womb / Erica Bastress-Dukehart -- Contested masculinity : noblemen and their mistresses in early modern Spain / Grace E. Coolidge -- Inventing the courtier in early sixteenth century Portugal / Susannah Humble Ferreira -- Sepulchral monuments as a means of communicating social and political power of nobles in early modern Russia / Cornelia Soldat -- Il monastero nuovo : cloistered women of the Medici court / Katherine L. Turner -- The question of the imprescriptibility of nobility in early modern France / Elie Haddad -- All the king's men : educational reform and the restoration of the service nobility in early seventeenth-century Spain / Ryan Gaston -- "Of polish'd pillars, or a roofe of gold" : authority and affluence in the English country house poem / Sukanya Dasgupta -- Nobility as a social and political dialogue : the Parisian example, 1650-1750 / Mathieu Marraud -- Challenging the status quo : attempts to modernize the Polish nobility in the later eighteenth century / Jerzy Lukowski -- Resilient notables : looking at the transformation of the Ottoman Empire from the local level / M. Safa Saraçoglu